The Impact of Strategic HRM Practices on the Performance of Guidance and Counseling Teachers within Islamic Educational Frameworks - Ahmad Daifi Al Farrozi; Muhyatun; Robbi Readi; Achmad Muhlis (Al-Qalam Institue, 2026)
This study aims to analyze the role of Strategic Human Resource Management (SHRM) in strengthening the performance of school counselors (Guidance and Counseling teachers) in Islamic educational institutions. This research employs a library research method, with data collected through a review of 30 relevant journal articles published within the last five years. Data analysis is conducted using a descriptive-analytical approach to gain an understanding of the integration between SHRM and counselor performance. The results indicate that counselor performance is a multidimensional construct influenced by both internal and external factors. This performance can be measured through key indicators, including the ability to plan guidance and counseling services, implement basic services, conduct individual and group counseling, engage in cross-professional collaboration, demonstrate understanding of professional ethics, manage administrative and counseling data, and carry out program evaluation and follow-up. All these indicators are closely related to SHRM pillars, namely competency-based recruitment and selection, continuous professional training and development, objective performance appraisal, and organizational support alongside a conducive work culture. This study emphasizes that strengthening counselor performance in Islamic educational institutions cannot be conducted partially but requires a systemic integration between performance indicators and SHRM practices.